Microcrédito e Pobreza: um Diálogo Possível? - Claire Gomes dos Santos (RAC: Revista de Administração Contemporânea, 2009)
Microcredit has been viewed by academics, as well as by multilateral organizations, as a viable alternative for facing the inequalities associated with worldization. However, its contribution is uncertain as a solution for a complex issue like poverty. The objective of this article, being theoretical in nature, is to discuss whether in the mainstream of the economic sciences the indication of microcredit as a strategy to fight against poverty prevails. The article is divided into three sections. In the first one, three different approaches of poverty are presented. The second one explores the notion of microcredit. Finally, the third section presents a reflection on the way poverty and microcredit have been related in the specialized literature. The article finishes with a few considerations.